Rekonstruksi Penyidikan dalam Sistem Peradilan Pidana Berbasis pada Prinsip Negara Hukum Pancasila - R, Mukhlis (Melayunesia Law, 2018)
The Criminal Procedure Code regulates Police Investigators as the main investigators and investigators of civil servants in coordination umbrella with Police Investigators. The development of laws outside the Criminal Code and Criminal Procedure Code regulates several Investigative Institutions (Police Investigators, Civil Service Investigators, Prosecutor Investigators, Corruption Eradication Commission Investigators, National Narcotics Agency Investigators, and Investigators of Financial Services Authorities). Differences in top management, as well as differences in authority and work in investigations, have led to conflicts between the Investigating Institutions, which have an effect on the achievement of the objectives of the integrated criminal justice system. In reality, the Investigative Institution consists of Police Investigators, Civil Service Investigators, Prosecutor Investigators, Corruption Eradication Commission Investigators, National Narcotics Agency Investigators, and Investigators of Financial Services Authorities. Each investigator has different top officials (Chief of Police, Attorney General, Minister of Law and Human Rights, Commander of the Indonesian National Army, Chairman of the Corruption Eradication Commission and Chairman of the National Narcotics Agency) and has different authority and conduct in conducting Investigations. Reconstruction of authority among the Investigating Institutions, conducted with Interpretation and Dialogue together which gave rise to new construction Pancasila Investigation Legal System.